Embodying the Artistic Spirit and the Prophetic Arts - Jennings, Willie James 1961- (2016)
This essay argues that the artistic mode and the prophetic mode are ways of life that must be joined today in order to establish and sustain a shared abundant life lived in freedom. The arts often give sight, sound, smell, touch, and taste to the depths of human life and the divine life. The prophetic mode of life sees what is going on and refuses to remain silent about what is seen and known. And joined to the artistic mode of life it plumbs the depths of what must be seen and known and extends the range and volume of what must be said. We need these joined modes of life at this moment in order to overcome two sophisticated modes of denial that characterise so much of contemporary life in the western world, the modes of concealment and consumption.